Cross-correlation of virome–bacteriome–host–metabolome to study respiratory health. Issue 1 (January 2022) - Iorio, Andrea; Biazzo, Manuele; Gardini, Simone; Muda, Andrea Onetti; Perno, Carlo Federico; Dallapiccola, Bruno; Putignani, Lorenza
Abstract : A comprehensive understanding of the microbiome–host relationship in respiratory diseases can be elucidated by exploring the landscape of virome–bacteriome–host metabolome data through unsupervised 'multi-omics' approaches. Here, we describe how the composition and function of airway and gut virome and bacteriome may contribute to pathogen establishment and propagation in airway districts and how the virome–bacteriome communities may react to respiratory diseases. A new systems medicine approach, including the characterization of respiratory and gut microbiome, may be crucial to demonstrate the likelihood and odds of respiratory disease pathophysiology, opening new avenues to the discovery of a chain of causation for key bacteria and viruses in disease severity. Highlights: The exploration of virome–bacteriome cross-correlations in the bidirectional microbiota–host framework is crucial to unveil the link to the severity and progression of respiratory infections. The study of the microbiome and its interactions with the host may help to discover and stratify features of respiratory diseases, including coronavirus disease 2019 (COVID-19) phenotypes. An understanding of the respiratory and gut microbiome may be useful to determine the likelihood of respiratory diseases in a timely and novel way, placing microbiomics as a reference discipline for infectious diseases in systems medicine. To distinguish causes and consequences between the structure–function of the microbiome and disease severity, it is necessary to establish a chain of causation for the role of key microorganisms in respiratory disease.